Impact of racism and discrimination on physical and mental health among Aboriginal and Torres Strait islander peoples living in Australia: a systematic scoping review - Camila A. Kairuz; Lisa M. Casanelia; Keziah Bennett-Brook; Julieann Coombes; Uday Narayan Yadav (BMC, 2021)
Abstract Background Racism is increasingly recognised as a significant health determinant that contributes to health inequalities. In Australia efforts have been made to bridge the recognised health gap between Aboriginal and Torres Strait Islander people and other Australians. This systematic scoping review aimed to assess, synthesise, and analyse the evidence in Australia about the impacts of racism on the mental and physical health of Aboriginal and Torrens Strait Islander peoples. Methods A systematic search was conducted to locate Australian studies in English published between 2000 and 2020. Five electronic databases were used: PubMed, CINAHL, Embase, Web of Science and the Australia's National Institute for Aboriginal and Torres Strait Islander Health Research. The search strategy included a combination of key words related with racism, mental health, physical health and Indigenous people. Data were extracted based on review questions and findings were synthesized in a narrative summary. Results Of total 338 searched studies from five databases, 12 studies met the inclusion criteria for narrative synthesis where eight were cross-sectional studies and four prospective cohorts. General mental health and general health perception were the most frequently studied outcomes followed by child behaviour, smoking and substance consumption and specific health conditions. The prevalence of racism varied between 6.9 and 97%. The most common health outcomes associated with racism were general poor mental health and poor general health perception. More specific health outcomes such as anxiety, depression, child behaviour, asthma, increased BMI and smoking were also associated with racism but were analysed by a limited number of studies. Three studies analysed psychological distress, negative mental health, sleeping difficulties and negative perceived mental health according to severity of exposition to racism. Conclusion Racism is associated with negative overall mental and negative general health outcomes among Aboriginal and Torres Strait Islander peoples. Strategies to prevent all forms and sources of racism are necessary to move forward to bridging the health gap between Aboriginal and Torres Strait Islander peoples and non-Indigenous Australians. Further research is needed to understand in more detail the impact of racism from an Aboriginal and Torres Strait Islander definition of health and wellbeing.